Iconic designs 50 stories about 50 things - Lees-Maffei, Grace (Bloomsbury Visual Arts, 2020)
"By returning to the etymological roots of iconicity and showcasing objects which are distinctive, memorable, internationally recognised and the subject of significant media attention, this text addresses what we mean by 'iconic' and how that aids our understanding of design and of iconicity. 50 compact chapters examine designs ranging from everyday goods to high-end 'designer' objects and explores how iconicity was established and how it contributes to our understanding of iconic design, by considering production, consumption and legacy alongside similar or contemporaneous objects. The book is divided into five parts, each addressing a thematic locus, arranged in a sequence from the public to the personal. This structure demonstrates that icons are not only a public phenomenon but infiltrate our intimate self-identity, in the form of objects which we carry with us and contribute to our sense of self. With significantly longer object entries than standard texts, this is essential reading for students and scholars of design history, design criticism, design studies and material culture studies, museum studies, art and architectural history, architecture and design practice"--